Assessment of Economic Indicators for Evaluation of Financial Performance - COCOŞILĂ, Mihaela (Journal of Advanced Studies in Finance, 2016)
The term performance is used as a general measure in different fields of activity. But, in fact, the term of economic performance includes a series of approaches and methods for quantifying, which differ especially according to the person who appreciates the performance. There are classical ratios of performance measurement, to which research literature has assigned a wide range of analysis and there are modern financial ratios, too. Concerning modern financial ratios, it is easy to measure the companies performance from the point of view of its shareholders and it is difficult to measure it from the point of view of the other company’s partners, because the satisfaction of these collaborators concerning the company is appreciated on the strength of some unmeasurable criteria or on the strength of some difficult to measure criteria: (the confidence in the company, the quality agreement with the company, the tradition of the businesss firms etc ). In a competitional environment, the performance cannot be presented without being placed in the context of some essential economic imperatives, that is effectiveness and efficacity. Any business plan involves an investment which has a consequence the expected result of the investor. The bigger is the result, the more new resources can appear which will be available for other investments for different purposes: the collaborators’ encouragement, the individual development, the resource creation system.
Keywords: effectiveness, performance, efficiency, result